Long‐term outcome of liver transplant patients with Budd‐Chiari syndrome secondary to myeloproliferative neoplasms. (31st March 2015) - Potthoff, Andrej; Attia, Dina; Pischke, Sven; Mederacke, Ingmar; Beutel, Gernot; Rifai, Kinan; Deterding, Katja; Heiringhoff, Karlheinz; Klempnauer, Jürgen; Strassburg, Christian P.; Manns, Michael P.; Bahr, Matthias J.
Abstract Background A considerable proportion of patients receiving liver transplants for Budd‐Chiari syndrome (BCS) suffer from myeloproliferative neoplasms (MPN). This study evaluated the long‐term prognosis of liver‐transplanted patients with BCS secondary to MPN and the effect of immunosuppression on MPN progression. Methods A total of 78 patients with BCS were evaluated between 1982 and 2013. Of those, 40 patients suffered from polycythaemia vera (PV) and essential thrombocythaemia (ET). One patient had primary myelofibrosis (PMF). All patients received the standard immunosuppressive regimen. We retrospectively evaluated the long‐term survival, clinical course and laboratory parameters of patients with MPN. Results Exactly 29/41 patients (71%) with MPN survived ≥ 3 years [mean age 36 ± 11 years; females n = 27 (93%)]. Mean follow‐up after orthotopic liver transplantation (OLT) was 12.4 ± 7.3 years (range 3–28 years). Five‐ and 10‐year survival rates were not significantly different in patients with and without MPN (P = 0.81 and P = 0.66 respectively) or in patients with PV and ET (P = 0.29 and P = 0.55 respectively). Thrombosis and bleeding developed in 7/29 (24%) long‐term MPN survivors with no significant difference between ET and PV (P = 0.18). In the long‐term follow‐up, there was no evidence of progression to overt myelofibrosis or acute myeloid leukaemia (AML). In the uni‐ and multivariate Cox‐regression analyses, MPN did not influence survival after OLT. Conclusions Budd‐Chiari syndrome patients with and without underlying MPN had similar long‐term survival rates after OLT. There was no evidence of enhanced progression of MPN after OLT secondary to immunosuppressive therapy. However, major haemorrhage and recurrent thrombosis contributed to morbidity and mortality after OLT in those patients.